Effectiveness of Quizz based Edugame as Learning Support Media for Improvement of Learning Outcomes - Sariyanto, Slamet; Suprayitno, Iswahyudi Joko; Sulistyaningsih, Dwi (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
The study discusses the effectiveness of using quiz-based edugame to improve student learning outcomes in the context of increasingly rapid technological developments. The negative impact of technology in the world of education is the decline of students' interest in learning because they are more interested in playing games than learning. Therefore, the emergence of innovation to use games as educational materials to attract student interest and motivation. The purpose of this study was to determine the impact of using edugame as learning media on students' learning outcomes. The method in this study uses the SLR (systematic literature review) method by analyzing articles from google scholar in the publication year 2021-2025 with a focus on the use of edugame in formal learning at the elementary, junior high, and high school levels. This study only covers Android-based or digital edugame and does not examine in depth external factors such as economic background or parental support for the effectiveness of edugame. The results of the analysis show that the use of quiz-based edugame has a positive impact where the increase in students' learning outcomes reaches 13.7% to 35% compared to usual learning, besides that edugame also increase students' interest and motivation to learn, therefore edugame can be an alternative for educators to utilize in an effort to improve students' learning outcomes.